Organizational Commitment, Employee Engagement, and Employee Performance: A Literature Review - Akhmad Tarmizi; Sarfilianty Anggian (Dinasti Publisher, 2022)
The aim of this paper is to provide a structured literature review on the constructs of organizational commitment, employee engagement, employee performance, and empirical evidence on the relationship between organizational commitment, employee engagement, and employee performance. 24 (twenty four) papers published during 2017-2022 that investigates organizational commitment, employee engagement, employee performance, and the relationship between organizational commitment, employee engagement, employee performance were reviewed. The results of the review show that organizational commitment and employee engagement have positive and significant effect on employee performance.